Influence of different Oryza cultivars on expression of nifH gene pools in roots of rice - Knauth, Stefan; Hurek, Thomas; Brar, Darshan; Reinhold-Hurek, Barbara (Wiley, 2005)
Cultivation‐independent studies suggest that roots of rice (Oryza sativa) are colonized by a diverse community of nitrogen‐fixing bacteria. Here we report for the first time mRNA‐based profiling of nitrogenase (nifH) genes, to study the impact of lowland‐rice genotypes at the cultivar level on the functional diversity of root‐associated diazotrophs. Root RNA extracts from all plants contained nifH mRNA at levels detectable by reverse transcription polymerase chain reaction (RT‐PCR). Terminal restriction fragment length polymorphism (T‐RFLP) analysis of RT‐PCR products showed only small interplant variations. However, RNA‐ and DNA‐based profiles obtained from the same root extractions differed from each other, suggesting that presence of diazotrophs did not necessarily coincide with active transcription of nif genes. Application of N‐fertilizer at planting had a long‐term effect on the profile of expressed nitrogenase genes. Phylogenetic analysis of a clone library constructed for nifH fragments expressed in wild species of rice roots indicated that active diazotrophs were not related to cultured strains. The composition of active diazotrophic communities was compared for six related cultivars of O. sativa, wild species Oryza brachyantha, and a genetic cross between it and cv. IR56, grown under identical conditions in rice field soil in the Philippines without N‐fertilizer application. Remarkable varietal differences in root associated nifH‐gene expressing communities were detected. This underlines the importance of mRNA‐based approaches to study functional diversity and eventually identify key diazotrophs in a particular environment.